2016
DOI: 10.1115/1.4033794
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Behaviors in Three Types of Spinal Cord Injury Mechanisms

Abstract: Clinically, spinal cord injuries (SCIs) are radiographically evaluated and diagnosed from plain radiographs, computed tomography (CT), and magnetic resonance imaging. However, it is difficult to conclude that radiographic evaluation of SCI can directly explain the fundamental mechanism of spinal cord damage. The von-Mises stress and maximum principal strain are directly associated with neurological damage in the spinal cord from a biomechanical viewpoint. In this study, the von-Mises stress and maximum princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…This shows that regardless of the assumptions made on the WM and GM material properties, it is possible to simulate the global mechanical behavior of the spinal cord. The three sets were chosen in view of the available data and have all been used in spinal cord FE model investigating injury mechanisms [12,13,18,[32][33][34]. This study demonstrated the strong impact of the choice of material properties on the local mechanical behavior throughout the spinal cord.…”
Section: Plos Onementioning
confidence: 99%
“…This shows that regardless of the assumptions made on the WM and GM material properties, it is possible to simulate the global mechanical behavior of the spinal cord. The three sets were chosen in view of the available data and have all been used in spinal cord FE model investigating injury mechanisms [12,13,18,[32][33][34]. This study demonstrated the strong impact of the choice of material properties on the local mechanical behavior throughout the spinal cord.…”
Section: Plos Onementioning
confidence: 99%
“…The maximum Von Mises value (3.8 kPa) are respectively 5, 33 and 86 times less than the ones in a contusion, a distraction and a dislocation at the C4/ C5 functional unit (Khuyagbaatar et al 2016).…”
Section: Resultsmentioning
confidence: 74%
“…There were some limitations in this study. The model used in this study was developed based on our previously validated FE model of the spinal cord 20,27 and indirectly validated by comparing the stresses and strain value in the spinal cord with those in previous computational studies. 25 Only one segmental type of OPLL at C5 was investigated, despite there being multiple factors related to clinical outcomes such as the OPLL, segmental mobility, and cervical lordosis.…”
Section: Discussionmentioning
confidence: 99%
“…Influence of flexion motion on the spinal cord was investigated, 16 and the hyperextension injury of the cervical spinal cord was analyzed in simple cases. 17 Moreover, the stress and strain distributions in the spinal cord were simulated during various column injury patterns, [18][19][20] ossified ligaments, [21][22][23][24] and contusion injuries. 14,[25][26][27][28] In our previous study, an FE model of the cervical spine with the spinal cord, including white matter, gray matter, dura mater with nerve roots, denticulate ligaments, and cerebrospinal fluid (CSF), was developed and investigated the effect of surgical extents in three different decompression methods on changes in stress, strain, and posterior shift of the spinal cord for cervical OPLL.…”
Section: Introductionmentioning
confidence: 99%